Brazilian species dynamic properties determination on short length-to-height wood pieces - Silva, João Vítor Felippe [UNESP]; Molina, Julio Cesar [UNESP] (My University, 2021)
This paper aimed to evaluate the dynamic properties of short length-to-height wood pieces according to current available impulse excitation standardized methodology. Experimental tests were performed according to standard ASTM E1876-15, considering four species of Brazilian reforestation wood. Species density and static stiffness were determined. The current available equations proved to be unsuitable for achieving reliable dynamic properties of wood, due to the non-converging correction factor using Poisson's ratio iterative methodology. The development of a mathematical model for dynamic properties determination of non-isotropic materials is recommended.
Keywords: Density; Impulse excitation method; Natural frequency; Non-destructive evaluation